Modern trends in the study of economic theory - Ortikov, Eldor (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Economic theory is a general economic and theoretical science that studies the principles, concepts and principles of economic development. Economic theory is called "Economics", "Economics" and "Political Economy" in foreign countries, and "Economic Theory" in the CIS. Economic theory studies economics in general and applied to each economic system, analyzes economic events at the micro and macro levels, as well as at the level of the world economy. In Uzbekistan, this subject is studied in schools as "Fundamentals of Economic Knowledge", in colleges and academic lyceums as "Fundamentals of Economics" and in higher education institutions as "Economic Theory"